CAPABIIITY OF FORGING TECHNIQUE TO PRODUCE ROUND SHAPE FLANGE USING (POM) MATERIAL UNDER COLD AND HOT CONDITIONS - Talib.H. Rashid (Journal of Engineering, 2024)
The paper studied capability o f forging proces s to produce round shape flange using ace t al (celcon celconR polymer w hich is an engineering crystalline material having a good ductility if it is preheated The process done under cold & hot conditions Th i s kind of technique guarantees a produc t with high strength and stiffness better than what injection molding could achieve . The products showed crack and curling traces on the flange under cold forging, but a good product was achieved by heating the billet and the tools to (100 C o with i mprovem ent in the mechanical properties The paper discussed also through stress strain c urves manner of deformation through forging action . The results explained that POM (celcon celconR) is forgeable polymer if it is preheated at 100 C o ) using slow speed pre ss by closed die forging process under applied pressure of 170 Mpa to produce round shape flange, while this technique f ailed to forge same polymer at room temperature.